USO DE AGENTES NA DETECÇÃO DE FRAUDES EM IMPOSTO MUNICIPAL - ISS - Sampaio, Cláudio Henrique Carneiro (2007)
This paper aims at detecting frauds in municipal taxes, using a multi-agent system. To attain such objective, it presents some of the stages of the software development and the implementation of some agents. The paper also proposes the behavior modeling of contributors, obtained from historical data from their actions and from behavior inference functions. That model, after being validated, with the use of data from São Luís County Hall, was transformed in agent. In the stages of analysis and design of the system, the methodologies MAS-Common KADS and the ontology ONTOMADEM (this one based in MADEM Multi-Agent Domain Engineering Methodology), were used. In the stage of development, JADE (Java Agent Development Framework) ambience and the PROTÉGÉ for JADE plug-ins were used, besides JESS, used to implement the ontologies and the rules.